Constructing Three-Phase Capillary Pressure Functions by Parameter Matching Using a Modified Ensemble Kalman Filter (Communications in Computational Physics, 2009)
Usually extended two-phase capillary pressures are used in three-phase simulations,because three-phase capillary pressures are not possible or hard to measure.In this work three-phase capillary pressure surfaces are created by at pore networkmodel. The input parameters to this network model are found by matching two-phasecapillary pressure curves. This matching is done with a slightly modified EnKF routine.Tables with three-phase capillary pressures are created and used as input to flowsimulations.